GASTRIC DUPLICATION CYST: A RARE CONGENITAL ANOMALY CAUSING GASTRIC OUTLET OBSTRUCTION - Khan khattak, Muhammad Adnan; Nisar, Muhammad Umar; Sikander, Samer; Akthar, Nadeem (Journal of Ayub Medical College Abbottabad, 2019)
Gastrointestinal duplication cyst is a rare congenital anomaly with a reported incidence of 1 in 4500 live births. Any part of gastrointestinal tract from mouth to anus can be affected with this anomaly. Among gastrointestinal tract duplications, gastric duplication cyst is extremely rare (2-9%). We are presenting a case of the stomach duplication in a four (04) day old male child who presented in our Emergency Department with complaints of non-bilious, non-projectile vomiting and visible bulge in upper abdomen since birth. Workup showed enteric duplication cyst which was excised. Complete surgical resection is the treatment of choice in gastric duplication cyst. Keywords: gastrointestinal duplication; alimentary tract duplication; gastric outlet obstruction; Pakistan